2020
DOI: 10.1007/s10992-020-09549-6
|View full text |Cite
|
Sign up to set email alerts
|

De Finettian Logics of Indicative Conditionals Part I: Trivalent Semantics and Validity

Abstract: This paper explores trivalent truth conditions for indicative conditionals, examining the "defective" truth table proposed by de Finetti (1936) and Reichenbach (1935, 1944). On their approach, a conditional takes the value of its consequent whenever its antecedent is true, and the value Indeterminate otherwise. Here we deal with the problem of selecting an adequate notion of validity for this conditional. We show that all standard validity schemes based on de Finetti's table come with some problems, and highli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 74 publications
(164 reference statements)
1
46
0
Order By: Relevance
“…Third: as it has already been advanced since Footnote 16, mccLP is the same logic as the one named DF/TT in Egré et al. ( 2021 ), in the sense that they validate exactly the same set of valid arguments. The authors did not notice all its contra-classical potential, though—besides connexivity, they just discussed the validity of .…”
Section: A Multi-contra-classical Variant Of Lpmentioning
confidence: 94%
See 3 more Smart Citations
“…Third: as it has already been advanced since Footnote 16, mccLP is the same logic as the one named DF/TT in Egré et al. ( 2021 ), in the sense that they validate exactly the same set of valid arguments. The authors did not notice all its contra-classical potential, though—besides connexivity, they just discussed the validity of .…”
Section: A Multi-contra-classical Variant Of Lpmentioning
confidence: 94%
“…DF/TT in Egré et al. ( 2021 ) has been extensively studied as a logic suitable for suppositional reasoning, that is, as a logic where conditionals are read as expressing conditional degrees of belief. Thus, mccLP at least opens the door for studying suppositional reasoning from the point of view of inconsistent degrees of belief.…”
Section: A Multi-contra-classical Variant Of Lpmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Egré et al. ( 2021 ) have shown that quasi-implication belongs to a family of intended conditionals > such that, with T-consequence will fail at least one of the following: Detachment, Self-identity, Non-symmetry ( ) or Non-entailment of conjunction ( ). Nonetheless, they have also shown that quasi-implication plus TT-consequence , that is…”
Section: R3v and Contra-classical Logicsmentioning
confidence: 99%